2018
DOI: 10.1055/a-0648-8874
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an ice hockey-specific complex test

Abstract: The IHCT is currently the only ice hockey-specific complex test with scientifically tested reliability and validity that can analyze performance under conditions similar to competition. It is suggested that coaches, fitness coaches and sports scientists explore use of this test as a valid tool to assess players' performance and the effectiveness of training interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The order of the different tasks had no influence on the intrarater reliability of the tasks and parameters. Schwesig et al [17] found no differences for the last skating tasks (weave agility without and with the puck). Only the 10 m backward sprint without a puck displayed a markedly reduced reliability (ICC = 0.54, coefficient of variation (CV) = 9.2%).…”
Section: Study Design and Methodologymentioning
confidence: 94%
See 4 more Smart Citations
“…The order of the different tasks had no influence on the intrarater reliability of the tasks and parameters. Schwesig et al [17] found no differences for the last skating tasks (weave agility without and with the puck). Only the 10 m backward sprint without a puck displayed a markedly reduced reliability (ICC = 0.54, coefficient of variation (CV) = 9.2%).…”
Section: Study Design and Methodologymentioning
confidence: 94%
“…Only the 10 m backward sprint without a puck displayed a markedly reduced reliability (ICC = 0.54, coefficient of variation (CV) = 9.2%). Reliability was slightly reduced for three parameters (10 m sprint with puck, slap shot 3 before test, slap shot 1 after test) (ICC: 0.60-0.73; CV: 5.0-8.3%) [17]. All players were assessed on the same day, and the tests were performed in the same order.…”
Section: Study Design and Methodologymentioning
confidence: 99%
See 3 more Smart Citations